Spatiotemporally controlled induction of gene expression in vivo allows tracking the fate of tumor cells that traffic through the lymphatics - Grau, Nicole; Scherer, Sandra; Rothley, Melanie; Roßwag, Sven; Thiele, Wilko; Stoecklein, Nikolas H.; Cremers, Natascha; Thaler, Sonja; Garvalov, Boyan K.; Sleeman, Jonathan P. (International journal of cancer, 2020)
Metastasis is a multistep process, during which circulating tumor cells traffic through diverse anatomical locations. Stable inducible marking of tumor cells in a manner that is tightly spatially and temporally controlled would allow tracking the contribution of cells passing through specific locations to metastatic dissemination. For example, tumor cells enter the lymphatic system and can form metastases in regional lymph nodes, but the relative contribution of tumor cells that traffic through the lymphatic system to the formation of distant metastases remains controversial. Here, we developed a novel genetic switch based on mild transient warming (TW) that allows cells to be marked in a defined spatiotemporal manner in vivo. Prior to warming, cells express only EGFP. Upon TW, the EGFP gene is excised and expression of mCherry is permanently turned on. We employed this system in an experimental pancreatic cancer model and used localized TW to induce the genetic switch in tumor cells trafficking through tumor-draining lymph nodes. Thereby we found that tumor cells disseminating via the lymphatics make a major contribution to the seeding of lung metastases. The inducible genetic marking system we have developed is a powerful tool for the tracking of metastasizing cells in vivo.
First published: 01 November 2019
Gesehen am 19.01.2021